PERBEDAAN KINERJA PERUSAHAAN SEBELUM DAN SESUDAH MERGER DAN AKUISISI, SERTA FAKTOR-FAKTOR YANG MEMPENGARUHI KINERJA PERUSAHAAN SETELAH MERGER DAN AKUISISI - , ALI RIZA FAHLEVI, Irfan Nursasmito, M.Si, aK. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This research tried to explains how the best companies in implementing decisions related to strategic M&As in improving company performance. The results in this study indicate that there are differences in firm market performance before and after doing M&As, otherwise there is no difference in operating performance before and after doing M&As. The study also describes the factors that affect the performance of the company after doing M&As. Associated with the performance of the company after doing M&As, this study revealed that the firm age effect on the performance of the bidders enterprise market, and the method of financing (stock/cash) effect on the operational performance of the company after doing M&As.